Dissolved Trace Metals in the Ross Sea - Gerringa, Loes J. A.; Alderkamp, Anne-Carlijn; van Dijken, Gert; Laan, Patrick; Middag, Rob; Arrigo, Kevin R. (Frontiers in Marine Science, 2020)
The dissolved (D) trace metals zinc (Zn), cadmium (Cd), cobalt (Co), copper (Cu), iron (Fe), manganese (Mn), nickel (Ni), titanium (Ti), lanthanum (La), Yttrium (Y) and lead (Pb) were analysed via ICPMS in samples from the Ross Sea obtained during a cruise between 20 December 2013 and 5 January 2014. The concentrations of DZn, DCd, DCo, DCu, DFe, DMn, DNi and DTi were significantly lower in the Antarctic surface Water (AASW) compared to the other deeper water masses, indicating biological uptake and possibly scavenging. In the AASW, DLa and DY were higher than in Winter Water (WW). This can be explained by a spring source from ice melt followed by loss during summer and autumn, probably due to passive adsorption. Dissolved Pb was low (16 pM) and no distinction between water masses was possible. Akin to the macro-nutrients nitrate and silicate, the modified Circumpolar Deep Water (mCDW) shows elevated DCd compared to the shelf water masses. Sea ice melt and ice sheet melt released DZn, DFe, DMn, DNi, DY, DLa, and probably DPb into the Ross Sea. However, only DFe, DMn, DY and DLa are transported into the Antarctic Circumpolar Current (ACC) with the outflowing High Salinity Shelf Water (HSSW). The bottom nepheloid layer (BNL) released DFe, as well as DMn and DCu, into the HSSW whereas lateral transport from land formed a source of DMn and DFe. One station in the Ross Sea polynya was resampled after two weeks, during which time the thickness of the BNL increased, with accompanying increases in DFe and DMn near the seafloor. In the surface layer nutrients (including micro-nutrients) were depleted further. The uptake slopes/stoichiometric ratios of DZn, DCd and DCo versus phosphate indicated that the distribution of these metals is related to uptake as well as the composition of the phytoplankton community. Estimated stoichiometric ratios of Zn and Cd relative to P were higher at a station dominated by Phaeocystis antarctica than at diatom-dominated stations, implying a higher utilisation of these metals by P. antarctica.